Experimental and DFT study of GO-decorated CaO quantum dots for catalytic dye degradation and bactericidal potential - Khan, Mahreen; Ikram, Muhammad; Haider, Ali; Ul-Hamid, Anwar; Ullah, Hameed; Shahzadi, Iram; Khan, Sherdil; Kanoun, Mohammed Benali; Goumri-Said, Souraya; Medina, Francisco; Nabgan, Walid (Frontiers in Environmental Science, 2023)
This research lays the groundwork for preparing graphene oxide (GO) doped CaO nanocomposites for efficient antibacterial potential and dye degradation. The study aimed to reduce the recombination rate of electron-hole of CaO and improve charge transfer. This issue can be minimized by doping high surface area GO into CaO quantum dots (QDs). Herein, the one-pot co-precipitation technique has prepared various concentrations (1, 3, and 5 wt. %) of GO-doped into CaO. Characterization techniques were used to investigate optical, elemental analysis, microstructural, functional, and morphological properties. The addition of GO into QDs showed excellent catalytic activity (CA) to control sample CaO against methylene blue (MB) in basic and acidic media compared to the neutral. Synergistic effect of morphological alternation attributed to an increase in the mechanism of CA upon doping. Various concentrations of GO to QDs promised remarkable bactericidal potency against E. coli.